Pre-mRNA splicing and cancer: exon-mediated transcriptional amplification as an emerging hallmark of malignancy - Neetu Singh (QJM: An International Journal of Medicine, 2026)
Abstract Cancer progression is commonly interpreted through genetic mutation and clonal selection. While this framework explains many aspects of tumour initiation, it does not fully account for prolonged dormancy, late relapse, spatial heterogeneity or metastasis occurring without new driver mutations. Increasing evidence indicates that these behaviours are governed by reversible regulatory processes operating downstream of DNA sequence. Here, we advance an RNA-centric framework in which transcriptional reinforcement and RNA fate control jointly shape tumour evolution across time and space. We focus on exon-mediated activation of transcription starts (EMATS), a mechanism whereby efficient exon recognition stabilizes promoter-proximal RNA polymerase II, suppresses premature termination and amplifies transcription from weak or context-dependent promoters without requiring promoter mutation, enhancer rewiring or immediate protein output. The resulting transcripts are subsequently filtered through RNA fate checkpoints that determine nuclear retention, decay or persistence, uncoupling transcriptional activity from translation. Within this model, non-coding and non-canonical RNAs function as spatiotemporal reporters of tumour state, encoding when and where transcriptional programmes are engaged. RNA persistence enables tumour cells to remain transcriptionally primed under hypoxia, therapeutic pressure or immune surveillance, supporting dormancy and rapid reactivation. By reframing tumour evolution as RNA-state regulation, this framework provides a mechanistic basis for plasticity, relapse and therapy resistance, and highlights RNA states as clinically actionable biomarkers and vulnerabilities.